2023
DOI: 10.1071/sh23015
|View full text |Cite
|
Sign up to set email alerts
|

Gay, bisexual, and queer men’s confidence in the Undetectable equals Untransmittable HIV prevention message: longitudinal qualitative analysis of the sexual decision-making of pre-exposure prophylaxis users over time

Abstract: Background Our objective was to understand what gay, bisexual, and queer men (GBQM) who had experience using pre-exposure prophylaxis (PrEP) thought about the ‘Undetectable equals Untransmittable’ (U=U) message and how it informed their sexual decision-making over time. Methods We conducted annual longitudinal qualitative interviews (2020–22) with 17 current or former PrEP users as part of a mixed-methods implementation science study examining barriers and facilitators to PrEP awareness, access, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a longitudinal qualitative analysis conducted by Grace et al, the researchers examined the confidence levels of GBM who had experienced using pre-exposure prophylaxis in Canada regarding the U=U message. 6 The study found that participants' confidence in U=U increased over time, leading them to feel comfortable engaging in sexual activities with partners who had undetectable viral loads. However, it is important to note that some participants still harboured reservations and did not fully trust U=U.…”
Section: U=u Cascadementioning
confidence: 95%
“…In a longitudinal qualitative analysis conducted by Grace et al, the researchers examined the confidence levels of GBM who had experienced using pre-exposure prophylaxis in Canada regarding the U=U message. 6 The study found that participants' confidence in U=U increased over time, leading them to feel comfortable engaging in sexual activities with partners who had undetectable viral loads. However, it is important to note that some participants still harboured reservations and did not fully trust U=U.…”
Section: U=u Cascadementioning
confidence: 95%
“…There was widespread consensus that although awareness of U=U is increasing, knowledge and trust in U=U is uneven, and predominantly concentrated among people living with HIV who are connected to gay, bisexual and queer communities. 6,[12][13][14][15][16][17][18][19] Among other populations at heightened vulnerability to HIV acquisition, awareness and trust of U=U is more limited. [20][21][22] Participants identified a need for members of all priority populations, including women, Indigenous and First Nations peoples, racially minoritised groups, migrants, people who use drugs, and sex workers to be explicitly included in policies that utilise and promote U=U.…”
Section: Key Themes a Need For Targeted And Tailored Messagingmentioning
confidence: 99%